Hemoadsorption: a new tool in neurotoxic poisoning - Hernandez-Vaquero, J.; Repilado-Alvarez, A.; de la Flor, J. C.; Mata Forte, T. (Frontiers in Nephrology, 2025)
Although the use of neurotoxic agents as weapons of war (CWAs) or in terrorist attacks is relatively uncommon, it has been documented on several occasions in recent history, including the Syrian civil war, the Tokyo subway attack, and the Salisbury incident. The toxidrome associated with these agents is well described; however, treatment remains largely supportive, as effective antidotes are not currently available. Conventional renal replacement therapies (RRT), such as hemodialysis or continuous modalities, are not recommended for managing neurotoxic agent poisoning due to their toxicodynamic properties. In contrast, hemoadsorption (HA), especially when combined with CRRT, has shown promise in organophosphate (OP) pesticide poisonings. Given the chemical similarities between neurotoxic CWAs and OP, HA may represent a rational therapeutic option in selected cases. Notably, substantial differences exist among these agents in terms of onset of action, routes of exposure, and pharmacodynamics, which critically affect both treatment effectiveness and the availability of a therapeutic window. While the management of such exposures has traditionally fallen under military medical services, documented use in terrorist contexts underscores the importance of civilian healthcare professionals being familiar with current treatment options. This article reviews the pathophysiological mechanisms and key chemical properties of neurotoxic agents and evaluates the potential role of HA as an adjunctive therapy in the management of patients exposed to these CWAs.